Pharmacology, from Rudolf Buchheim to Arnold Holste: The founding of the Institute of Pharmacology at the Faculty of Medicine, University of Belgrade - Todorović Zoran; Vučković Sonja; Divac Nevena (Scripta Medica, 2022)
The School of Medicine at the University of Belgrade celebrates its centennial anniversary. The Institute of Pharmacology and Toxicology, founded in 1924, played an important role in the School's life and development. It is not just about the scientific achievements, but above all, the exceptional personalities of our predecessors. If they spent their academic careers somewhere else, they would certainly have been among the most respected researchers in the world. The courage to stay in the turbulent Balkans and maintain successful communication with colleagues from abroad deserves respect and admiration. One German and one Serb, professors Arnold Holste and Radivoje Pavlović, the latter with severely impaired sight, did an extraordinary job. They established a distinct pharmacological school, equipped research labs and provided their students with generous support despite the adverse circumstances (two world wars and persistent economic crisis, above all). Their younger associates, future professors Dimitrijević and Bogdanović, followed in the footsteps of their predecessors. Their example and sacrifice oblige us to keep pace with the extremely rapid development of pharmacology in the world.